Mao's road to power : revolutionary writings, 1912-49.: revolutionary writings, 1912-49. The rise and fall of the Chinese Soviet Republic, 1931-34 / Volume 4, (2016) - Mao, Zedong, 1893-1976; Schram, Stuart R (Stuart Reynolds), 1924-2012
No abstract available